Developing control points for halal slaughtering of poultry - Shahdan, Intan Azura; Regenstein, J.M.; Shahabuddin, A.S.M; Rahman, Mohammad Tariqur (Oxford University Press, 2016)
Halal (permissible or lawful) poultry meat production must meet industry, economic, and production needs, and government health requirements without compromising the Islamic religious requirements derived from the Qur'an and the Hadiths (the actions and sayings of the Prophet Muhammad, peace and blessings be upon him). Halal certification authorities may vary in their interpretation of these teachings, which leads to differences in halal slaughter requirements. The current study proposes 6 control points (CP) for halal poultry meat production based on the most commonly used halal production systems. CP 1 describes what is allowed and prohibited, such as blood and animal manure, and feed ingredients for halal poultry meat production. CP 2 describes the requirements for humane handling during lairage. CP 3 describes different methods for immobilizing poultry, when immobilization is used, such as water bath stunning. CP 4 describes the importance of intention, details of the halal slaughter, and the equipment permitted. CP 5 and CP 6 describe the requirements after the neck cut has been made such as the time needed before the carcasses can enter the scalding tank, and the potential for meat adulteration with fecal residues and blood. It is important to note that the proposed halal CP program is presented as a starting point for any individual halal certifying body to improve its practices.